Risk Perception of Nonspecific Low Back Pain among Nurses: A Qualitative Approach - Sedigheh Abedini; Mohammad Ali Morowatisharifabad; Behnaz Enjezab; Abolfazl Barkhordari; Hossein Fallahzadeh (Tabriz University of Medical Sciences, 2014)
Background:Low back pain (LBP) is a common medical problem among nurses. A better understanding of nurses' experiences about LBP may help to develop preventative approaches. The study aimed to explore risk perceptions of nonspecific LBP among nurses in Bandar Abbas City, southern Iran. Methods: This qualitative study conducted as directed content analysis in 2013. Private semi-structured interviews were conducted with a convenience sample of 30 nurses with minimum of 1-year working experience in hospital. The interview questions were based on perceived severity and vulnerability structures of Protection Motivation Theory. All interviews were transcribed and analyzed using thematic analysis. Results: Perceived Severity had the following sub-themes: developing disorders in one's own life and profession, psychical and mental consequences, conflicts and problems in family life, and financial problems. Two sub-themes (problems and limitations in hospital's working system, nature of nursing profession) were identified in relation to perceived vulnerability. Conclusion: Nurses reflected their concerns about the impact of LBP on their job security and their considerations about how their back pain might be interpreted by their employers and co-workers. Importance of transparent medical diagnostic procedure and clinical evidence to justify degree of LBP and its burden on the nurses' performance was also addressed.